Legal Protection for MSMEs Against Fictitious Orders in ShopeeFood - Atika Sunarto; Ruth Amanda Sinaremare; Selvina Siahaan; Muhammad Ali Adnan (JURNAL USM LAW REVIEW, 2026)
This study examines the legal protection of Micro, Small, and Medium Enterprises (MSMEs) against fictitious orders on the ShopeeFood platform, particularly within Cash on Delivery (COD) transactions that generate financial losses for merchants. The research employs a normative-empirical juridical method using statutory, conceptual, and case approaches supported by interviews with MSME actors in Medan City and analyses of relevant legal regulations and platform policies. The findings reveal that fictitious orders constitute a form of consumer default and, in certain circumstances, may also fulfill the elements of unlawful acts in electronic transactions because consumers intentionally fail to receive and pay for ordered goods. Although legal protection is normatively available through the Civil Code, Consumer Protection Law, and Electronic Information and Transactions Law, its implementation remains ineffective due to weak consumer verification systems, limited access to electronic evidence, unclear platform liability standards, and inadequate compensation mechanisms. The study further demonstrates that digital platforms cannot merely be regarded as passive intermediaries because they exercise substantial control over transaction systems, user data, payment mechanisms, and dispute resolution procedures. The novelty of this research lies in its integrative analysis of the relationship between consumer default, platform accountability, and MSME protection within app-based food delivery ecosystems through a combined normative and empirical approach. This study contributes theoretically to the development of digital commerce liability discourse and practically proposes a regulatory framework emphasizing stronger platform accountability, technology-based fraud prevention, mandatory user verification, merchant compensation mechanisms, and accessible online dispute resolution systems to strengthen legal certainty and substantive protection for MSMEs in Indonesia’s digital economy.